Lycium barbarum Extracts Extend Lifespan and Alleviate Proteotoxicity in Caenorhabditis elegans - Zhou, Haitao; Ding, Shanshan; Sun, Chuanxin; Fu, Jiahui; Yang, Dong; Wang, Xi'e; Wang, Chih-chen; Wang, Lei (Frontiers in Nutrition, 2022)
Lycium barbarum berry (Ningxia Gouqi, Fructus lycii, goji berry, or wolfberry), as a traditional Chinese herb, was recorded beneficial for longevity in traditional Chinese medical scriptures, and currently is a natural dietary supplement worldwide. However, under modern experimental conditions, the longevity effect of L. barbarum berry and the underlying mechanisms have been less studied. Here, we reported that total water extracts of L. barbarum berry (LBE), which contains 22% polysaccharides and other components, such as anthocyanins, extended the lifespan of Caenorhabditis elegans without side effects on worm fertility and pharyngeal pumping. Interestingly, we found that the lifespan extension effect was more prominent in worms with shorter mean lifespan as compared to those with longer mean lifespan. Furthermore, we showed that the lifespan extension effect of LBE depended on deacetylase sir-2.1. Remarkably, LBE rescued heat shock transcription factor-1 (hsf-1) deficiency in wild-type worms with different mean lifespan, and this effect also depended on sir-2.1. In addition, we found that LBE extended lifespan and alleviated toxic protein aggregation in neurodegenerative worms with hsf-1 deficiency. Our study suggested that LBE may be a potential anti-aging natural dietary supplement especially to individuals with malnutrition or chronic diseases, and a potential therapeutic agent for neurodegenerative diseases characterized by hsf-1 deficiency.